Analisis Pengaruh Diversifikasi Produk, Harga dan Citra Merek terhadap Keputusan Pembelian pada Mie Gacoan Cabang Bintaro - Martandani, Marcellus (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Mie Gacoan is a business that offers interesting and unique products because it not only offers various flavors for each product. However, the naming of each product is also very unique, such as suit noodles, hompimpa noodles, gacoan noodles, gobak Sodor ice, hide and seek ice and others. The public is generally interested because Mie Gacoan offers various levels of spicy taste that consumers can choose according to their taste. Another marketing strategy implemented by Mie Gacoan which is the cause of Mie Gacoan going viral is determining low product prices. For consumers, the price of Mie Gacoan products is considered very affordable or accessible to various groups, including young people who are even willing to wait in long queues. The brand image of the Mie Gacoan business is considered very easy to remember and recognize among young people because the unique Mie Gacoan logo design is displayed in front of the Me Gacoan restaurant. The packaging design for the Mie Gacoan wrapper product looks simple but still displays the unique character of the Mie Gacoan brand so that consumers don't get bored with mediocre designs. This very interesting restaurant concept creates a different experience for consumers who enter the restaurant.